Digital Services in Georgian Tourism – The Basis of Smart Tourism - Meladze, Maia; Gvaramadze, Ana; Bestaeva, Salome (European Scientific Journal, ESJ, 2024)
The paper is an integral part of the project "Research on the use of digital products in the Georgian tourism sector" which won the internal grant projects competition of Grigol Robakidze University. Digitalization is an inseparable part of the modern world. More and more companies are trying to refine and simplify both production and service. Digital technologies are helping companies in the tourism industry to expand the scope of their activities, covering a much larger scale than was previously possible. The use of digital technologies helps companies in the field of tourism not only to improve the service but also with its help the company can use online marketing, which significantly stimulates sales growth. There are a lot of essential modern digital trends that those in the tourism industry need to be aware of and adapt to if they are going to successfully optimize business performance. The objective of the chapter is to identify digital services in the Georgian tourism sector, determine the level of development of smart tourism, analyze its characteristics, and review challenges and opportunities in this direction.